The Impact of Isolation Measures during COVID-19 Pandemic on Russian Students' Motivation for Learning - Albina R. Drozdikova-Zaripova; Roza A. Valeeva; Niyaz R. Latypov (MDPI AG, 2021)
One of the leading problems of teaching is maintaining the students' motivation for learning. In the current epidemiological situation, improvement of education quality using digital platforms and educational services by creating conditions for increasing the learning motivation of students is an essential and relevant task. Therefore, the aim of the research was to study the motivation of the educational activity of junior students during the COVID-19 lockdown period and the development of effective approaches to increase the learning motivation of students in the context of distance learning using the Microsoft Teams platform. Research methods: Theoretical analysis of psychological and pedagogical literature, generalization; experiment, questioning, testing and data processing methods. In total, 107 undergraduates took part in the study. The difficulties and benefits that students encountered during the lockdown, as well as the attitude of students to the distance learning format, were revealed. There were specified dominant motivators, intentions and motives that determine the educational activity of students. We have presented approaches to the content management of the educational process in a distance format, with various ways and techniques of increasing the educational motivation of students under the conditions of distance learning.